2020
DOI: 10.1017/s0007114520000823
|View full text |Cite
|
Sign up to set email alerts
|

Assessing diet in a university student population: a longitudinal food card transaction data approach

Abstract: Starting university is an important time with respect to dietary changes. This study reports a novel approach to assessing student diet by utilising student-level food transaction data to explore dietary patterns. First-year students living in catered accommodation at the University of Leeds (UK) received pre-credited food cards for use in university catering facilities. Food card transaction data were obtained for semester 1, 2016 and linked with student age and sex. k-Means cluster analysis was applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Being data driven, using detailed food categories, they are more difficult to compare to patterns observed in other studies, generated from subjects with different consumption or purchasing behaviours. That said, there are common themes in our patterns seen in many other studies, for example: presence of a carnivore pattern, a sweet tooth/snacking pattern and a meat alternative, or vegetarian pattern [ 32 , 33 ]. Our patterns differ from many previous studies, due to the inclusion of alcohol in the cluster generating process, which we believe to be a strength as alcohol contributes to energy intake.…”
Section: Discussionmentioning
confidence: 77%
“…Being data driven, using detailed food categories, they are more difficult to compare to patterns observed in other studies, generated from subjects with different consumption or purchasing behaviours. That said, there are common themes in our patterns seen in many other studies, for example: presence of a carnivore pattern, a sweet tooth/snacking pattern and a meat alternative, or vegetarian pattern [ 32 , 33 ]. Our patterns differ from many previous studies, due to the inclusion of alcohol in the cluster generating process, which we believe to be a strength as alcohol contributes to energy intake.…”
Section: Discussionmentioning
confidence: 77%
“… 62 , 68 , 69 Transaction data have a number of strengths. Large data volumes enable data-driven exploration of dietary patterns 55–57 , 82 to better understand food-purchase behaviors and identify intervention target groups. Furthermore, continuous data collection permits observation and control for day to day, 83 week by week, 38 and seasonal variation in dietary choices, 59 which cannot be revealed in such detail by cross-sectional dietary surveys.…”
Section: Discussionmentioning
confidence: 99%
“…According to age group, gender, and BMI, the results were inconsistent. With respect to age group, various studies have shown that AMD increased as age did [ 18 , 25 ], but another study found no difference with age group [ 21 ]. In terms of gender, one study shows that females had higher adherence than males [ 4 ], while another study found that females had poorer adherence than males [ 21 ].…”
Section: Introductionmentioning
confidence: 99%